2008
DOI: 10.4161/cc.7.5.5427
|View full text |Cite
|
Sign up to set email alerts
|

Loss of neuronal cell cycle control as a mechanism of neurodegeneration in the Presenilin-1 Alzheimer's disease brain

Abstract: We show that cyclin D1 is indeed upregulated in cortical neurons of mice expressing the knock-in PS1 FAD mutation M146V, as well as in temporal cortex of FAD patients expressing different PS1 mutations. Cyclin D1 upregulation in mutant neurons leads to cell cycle-driven apoptosis, a phenotype reversed by blocking entry into the cell cycle by small interfering RNA (siRNA) cyclin D1 downregulation and by treatment with the cell cycle inhibitor quercetin, but not by γ-secretase inhibition. Furthermore, β-catenin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 31 publications
4
46
0
Order By: Relevance
“…A recent study reported that neurons harboring the PS1 M146V FAD mutation show enhanced neuronal apoptosis associated with abnormal induction of neuronal cell cycle proteins. 42 Consistent with the role of PS-dependent regulation of PML, significantly increased levels of PML protein and mRNA were observed in samples from AD patients (FAD and SAD) compared with controls (Figures 7a and b). Interestingly, polarized PML expression was also observed in SAD patients, suggesting Reagents and antibodies.…”
Section: Discussionsupporting
confidence: 80%
“…A recent study reported that neurons harboring the PS1 M146V FAD mutation show enhanced neuronal apoptosis associated with abnormal induction of neuronal cell cycle proteins. 42 Consistent with the role of PS-dependent regulation of PML, significantly increased levels of PML protein and mRNA were observed in samples from AD patients (FAD and SAD) compared with controls (Figures 7a and b). Interestingly, polarized PML expression was also observed in SAD patients, suggesting Reagents and antibodies.…”
Section: Discussionsupporting
confidence: 80%
“…Cyclin D1, which is expressed in very small amounts in terminally differentiated neurons, is elevated in response to neurotoxic stimuli, contributing to the process of CRNA (12,18). In addition, cyclin D1 is aberrantly expressed in patients with mild cognitive impairment and AD (11).…”
Section: Resultsmentioning
confidence: 99%
“…In response to neurotoxic insults like amyloid peptide A␤ 42 , the aberrant expression of cell cycle proteins like cyclins facilitates cell cycle reentry (15)(16)(17). In this context, cyclin D1 seems to play an important role in cell cycle-related neuronal apoptosis (CRNA), as its increased expression by A␤ 42 or DNA-damaging agents triggers this process (12,16,18). In addition, cyclin D1 is highly expressed in neurons of patients with mild cognitive impairment (MCI) and AD, which undergo CRNA (11).…”
mentioning
confidence: 99%
“…To detect SH-SY5Y cells in S phase of the cell cycle, 10 μM of 5′-bromo-2′-doxyuridine (BrdU, Sigma) was added to the culture medium for 2 h 30 min, cells fixed, and assessed for BrdU incorporation as previously described (Malik et al 2008). Nuclei were counterstained with Hoechst 33,342 (Invitrogen) to assay for total cell numbers.…”
Section: Brdu Incorporation Assaymentioning
confidence: 99%